Poruchy chování u sedmiletých detí-- výsledky studie ELSPAC. 3. Vývoj v období po narození - Kukla, L; Hrubá, D; Tyrlík, M; Matejová, H (Casopis lekaru ceskych, 2008)
BACKGROUND: In the European Longitudinal Study of Pregnancy and Childhood (ELSPAC), the pediatric observation of the cohort of 6100 7-year-old children described 4.4% of them as having conduct disorders. METHODS AND RESULTS: The predominant markers such as strong negativism, aggressivity, attention deficit, non-adequate reactions, hyperactivity, disorders of psychomotoric development, school maturation delay, poorer school results and social adaptation described children behavioral problems. The first signs of conduct disorders were often discovered already at the 18th month and the 3rd year of children's age. The acceptance of standardized criteria of possible conduct disorders in the routine pediatric practice, and the special psychologic and/or psychiatric care for children with the confirmed diagnosis should be recommended as soon as in their toddler age. CONCLUSIONS: Possible causal associations between prenatal exposure to nicotine and conduct disorders in childhood are another strong reason for the primary prevention and smoking cessation in antenatal clinics.
Keywords: kouření; vztahy mezi matkou a dítětem; Conduct Disorder; porucha chování; Smoking; Mother-Child Relations; lidé; Female; Infant; Pregnancy; předškolní dítě; těhotenství; kojenec; zpožděný efekt prenatální expozice; Child, Preschool; Prenatal Exposure Delayed Effects; ženské pohlaví; Humans